MECHANICAL PROPERTIES AND MICROSTRUCTURE OF EPOXY, HORN, ALKALINE TREATED/UNTREATED COCONUT SHELL PARTICULATES HYBRID COMPOSITE - Ajao, Kabiru; Abdulrahman, Salawu; Abdulkareem, Ambali (FUDMA Journal of Sciences, 2024)
ABSTRACT: The mechanical properties (Tensile and Flexural Strengths) of sheep horn, treated and untreated coconut shell particles reinforced epoxy composite were investigated in this work. The composite was formulated using design expert software, with weight fraction of epoxy resin varied from 90 to 100%, while that of each of the sheep horn and coconut shell particles varied from 0 to 5 % weight, resulting in the composite of single and hybrid reinforcements. The results obtained showed that tensile and flexural strengths of the hybrid composite were superior to those of the individual fiber reinforced composite. Maximum tensile strength and flexural strength of 36.52 MPa and 67.93 MPa respectively, representing 74.3%, and 35.6% improvement, compared to the tensile strength and flexural strength of the control sample were obtained with the hybrid composite sample containing a blend of 5% wt. sheep horn and 3% wt. treated coconut shell particles. The microstructure analysis revealed the enhanced interfacial adhesion between the matrix and the reinforcement of the composite samples containing alkaline treated coconut shell particles. Hence, alkaline treatment is a good natural fiber’s surface modification technique to improve adhesion between the fibers and the matrix.